The Effect of Palm Fronds Waste Ash Particulate on the Mechanical, Thermal and Acoustic Insulation Features of Polymeric Composites - Ahmed, Zainab; Adil I. Kadim; Mahbubur M. Rahman (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
We have used Palm frond base Ash Waste Particles as a natural, safe, and non-toxic reinforcing material to enhance and improve the characteristics of the epoxy polymer matrix. We utilized Palm frond base Ash Waste Particles as a natural, safe, and non-toxic reinforcing material to enhance the characteristics of the epoxy matrix. Ash Waste Particles were used in weight fractions of 0, 2.5, 5, 7.5, and 10%. The outcomes showed that the process of reinforcing with Ash Waste Particles increased the tensile strength from 8.782 MPa to 23.253 MPa. Additionally, the hardness value increased from 58.875 (Shore D.) to 74 (Shore D.). For the pure sample, the thermal conductivity has decreased to 0.135 Wm-1 0C-1 from 0.158 Wm-1 0C-1 . The transferred acoustic energy from side to side of the specimens (Acoustic Insulation Character) has reduced from 103.3 to 94.7 W⁄ m2 s. Finally, at the 10% weight fraction, the specimen's density value decreased from 1.557 to 1.208 g/cm3.